Incidence of Helminthosporium leaf blight of wheat and biochemical back-ground of disease resistance in the Eastern Gangetic Plains - Mukherjee, Soma; Chowdhury, A K; Bhattacharya, P M; Singh, Gyanendra (Journal of Cereal Research, 2011)
Helminthosporium leaf blight (HLB) caused by Bipolaris sorokiniana, is a major disease of wheat grown under humid subtropical climates. Germplasm lines were evaluated for their response against foliar blight disease. Overall recovery of B. sorokiniana population was significantly higher than A. triticina population. Among five different varieties tested, all showed almost similar results. Assay of polyphenoloxidase and peroxidase enzyme activities showed that following infection, a substantial increase in PPO activity and in PO activity were recorded in resistant germplasms whereas the corresponding values were lower in susceptible germplasms.